Effect of Severe Plastic Deformation on the Properties and Structural Developments of high purity Al and Al-Cu-Mg-Zr Aluminium Alloy - Kvačkaj, Tibor; Bidulská, Jana; Kočiško, Robert; Bidulský, Róbert (IntechOpen, 2011)
None